ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU IMPULSE BUYING : Studi Kasus Pada Generasi Z Pengguna E-Commerce - Mevi Venia, (2021)
The growth of e-commerce is influenced by the behavior of Indonesian consumers who want the convenience of shopping, and are starting interested in doing shopping online. Nowadays, generation Z is the generation that currently dominates shopping online compared to other generations. Currently, approximately 50% of total consumer expenditure is also influenced by technology which provides opportunities for quick and easy purchase options so as to create customers to make impulse buying. Generation Z in Indonesia is included in the characteristics of consumers who do impulse buying. Impulse buying can be affected by internal factors and external factors. This study aims to determine the effect of lifestyle, sales promotion and hedonic shopping motivation on impulse buying. This research is a quantitative research. The data in this study were obtained through a questionnaire and measured through a Likert scale using the Partial Least Square (PLS) method which was processed using SmartPLS 3.3.2 software. The sample used in this study were 96 people. The sampling technique used was purposive sampling method. The results of this study indicate that the lifestyle variable has a positive and significant effect on impulse buying of 0.179. Sales promotion has a positive and significant effect on impulse buying of 0.323 and hedonic shopping motivation has a positive and significant effect on 0.346 and the three variables in this study have a determination coefficient value of 0.464 or 46.4% in influencing impulse buying in generation Z.